The Influence of Problem Based Learning Model (PBL) Using Lesson Study (LS) Pattern on Quality of Chemistry Learning in SMAN 1 Banawa - Nur Hikmah; Paulus Hengky Abram; Suherman Suherman (Jurnal Akademika Kimia, 2019)
This study aimed to determine the effect of problem based learning model (PBL) using Lesson Study (LS) pattern on the quality of chemistry learning at SMAN 1 Banawa. This research type was a quasi-experiment with design equivalent pretest-posttest design. The sample used in this research was the students of class XI MIPA 3 as the experiment with the amount of 32 students and students of class XI MIPA 4 as the control class with the amount of 33 students. The result of data analysis obtained, the mean value of experiment class ( ) was 74.03 and the control class ( ) was 69.84. The average of students’ activity in the experimental and control class respectively was 56.66%, and 56.66% that was categorized as active enough. The result of hypothesis testing with two-party of t-test statistic obtained was –ttable< tcount> +ttable(tcount = 5.37 dan ttable = 1.67) with a significance level α = 0.05 and degrees of freedom 63, H0 was rejected and Ha was accepted based on the results of data analysis. So it can be concluded that there is influence of PBL model using LS pattern on the quality of chemistry learning in SMAN 1 Banawa.